Limitation of Administrative Authority of the Regional Office of the National Land Agency in the Cancellation of Land Rights Certificates - Abd. Rahman; Siti Hasanah; Yulias Erwin (Civiliza Publishing, 2026)
The existence of a certificate as proof of ownership does not automatically serve as the sole guarantee of legal certainty regarding a person’s ownership of land, as certificates often contain administrative and legal defects. This study aims to: 1) identify the limits of the administrative authority of the West Nusa Tenggara Provincial Office of the National Land Agency in revoking land title certificates in accordance with laws and regulations; 2) To examine and analyze the Decision of the West Nusa Tenggara Provincial Office of the National Land Agency No. 158/SK-52.MP.02.03/X/2022; and 3) To examine the legal implications of certificate revocation by the West Nusa Tenggara Provincial Office of the National Land Agency on legal certainty and the protection of land rights for certificate holders. The research approach used is the normative research method; specifically, this study employs a descriptive-analytical approach. The types and sources of data in this study include primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis method used is qualitative data analysis. The results of the study indicate that: (1) The administrative authority of the NTB Regional Office of the National Land Agency (BPN) to revoke certificates is strictly limited by Article 32(2) of Government Regulation No. 24 of 1997 regarding the five-year time limit and the exclusive jurisdiction of civil courts in ownership disputes. (2) Decision No. 158/SK-52.MP.02.03/X/2022 formally meets the legal requirements regarding authority but, in substance, violates the Principles of Legal Certainty and Diligence by revoking a certificate issued under a government program (PTSL) without a final and binding court decision. (3) The legal implications of this revocation are the loss of the certificate holder’s legal status and a weakening of public confidence in the legal certainty guaranteed by land certificates. It is recommended that regulations be harmonized so that administrative revocations continue to respect the substantive rights of citizens.